Pengaruh ISR, Leverage dan Likuiditas terhadap ERC pada Perusahaan yang Terdaftar di ISSI Tahun 2015-2020 - Ekawati, Evi; Yanti, Indri (Penerbit Goodwood, 2022)
Purpose: The purpose of this study is to find out whether Islamic Social Reporting has an effect on the Earning Response Coefficient, find out whether Leverage has an effect on the Earning Response Coefficient, and find out whether Liquidity has an effect on the Earning Response Coefficient. Method: This study uses quantitative research methods with secondary data types from 2015-2020 obtained from the IDX official website and Yahoo Finance. Data collection techniques used are documentation and library studies. The sampling technique used purposive sampling with a sample of 30 manufacturing companies. The data analysis used is panel data regression analysis with E-views software version 12. Result: The results of this study are Islamic Social Reporting, Leverage, and Liquidity have no effect on the Earnings Response Coefficient. This is because financial accounting standards do not require companies to disclose Islamic Social Reporting. Companies that have high debt may be because the company is growing and the company is able to pay off its short-term debt and run company operations to generate profits without fear of liquidation. Contribution: This research is expected to be used as input and consideration for investors and companies regarding the company's earnings response coefficient.